Quantum-Elliptic curve Cryptography for Multihop Communication in 5G Networks - Khan, A.S.; Johari, Abdullah; Khan, N.; Julahi, A.A.; Tarmizi, S. (IJCSNS, 2017)
The Internet of Things (IoT) depicts a giant network where every “thing” can be interconnected through the communication network. The communication can be initiated between people-people, people-things, and things-things. Meanwhile, the fifth generation (5G) mobile communicating systems are the mainspring to power the IoT concept in the upcoming future. However, the heterogeneous environment in 5G networks as well as the high dependency on radio spectrum have raised deep concerns about the security assurance against network attacks such as eavesdropping. In this paper, we propose an end-to-end security mechanism to ensure the multi-hop relay communications in 5G based IoT networks to stay secured. We design a scenario to explain the insecure multi-hop relay communications which involves Base Station (BS), Subscriber Station (SS) and Relay Station (RS). Next, we utilize Quantum Cryptography between BS to RS and RS to RS as well as adopting Elliptic Curve Cryptography between BS to SS or RS to SS to mitigate the network against typical replay attacks. By using the concept of integrating both cryptographic methods, the secret key that yield from Quantum Cryptography will be used in Elliptic Curve Cryptography to secure the transmission of information across IoT networks. Thereupon, extensive discussion has been carried out and it shows that the suggested mechanism has potential to ensure confidentiality, integrity, availability and non-repudiation in the proposed scenario. In the final part of this paper, we conclude our study by a comparison analysis between the two proposed cryptographic solutions. The comparison analysis illustrates the performance of each proposed strategy in terms of the achievable level of secrecy in IoT networks.